The National-Cultural Features of Nonverbal Means (Texas Journal of Multidisciplinary Studies, 2024)
In world linguistics, particularly in Uzbek linguistics, the study of nonverbal means of speech communication (various states in the voice, gestures, facial expressions, and body movements) has been carried out in different aspects of the language. Modern life realities show that communication in all societies of the current world is characterized by extreme freedom, unpredictability, and distance from language rules. The role of nonverbal tools has increased more than ever, taking on a significant pragmatic load. Notably, nonverbal tools in virtual communication remain unnoticed by researchers. This article provides a brief overview of virtual communication and its study's degree and significance. Nonverbal forms of communication are also extensively analyzed. Additionally, linguistic and non-linguistic relations, their interaction, and contradictions, as well as the possibility of creating a certain image, are discussed. The characteristics of nonverbal means in the communication process are also highlighted. Furthermore, it addresses the communication and interaction process in Uzbeks and the forms of communication used historically.